2020
DOI: 10.1155/2020/4127959
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative and Antioxidant Properties of Autologous Platelet-Rich Plasma Can Reserve the Aging Process of the Cornea in the Rat Model

Abstract: Aging is a natural progressive decline in the biological function of cells. Age-related changes in the cornea can affect its ability to refract light or repair itself. Platelet-rich plasma (PRP) has a promising role in regenerative medicine and evidenced its efficacy in multiple fields, but in corneal aging has not yet been elucidated. The present work was performed to estimate the regenerative antioxidant effect of PRP on corneal aging in rats. Rats were assigned into two main groups: (GI) adult group and (GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Platelets (PLT) secrete many GFs that play a major role in modulating cell pathways that promote tissue repair and remodeling. Moreover, it has also been demonstrated that PRP may promote tissue/cell homeostasis by counteracting the effects of OS in vivo [28,33,34] and in…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets (PLT) secrete many GFs that play a major role in modulating cell pathways that promote tissue repair and remodeling. Moreover, it has also been demonstrated that PRP may promote tissue/cell homeostasis by counteracting the effects of OS in vivo [28,33,34] and in…”
Section: Discussionmentioning
confidence: 99%
“…Platelets (PLT) secrete many GFs that play a major role in modulating cell pathways that promote tissue repair and remodeling. Moreover, it has also been demonstrated that PRP may promote tissue/cell homeostasis by counteracting the effects of OS in vivo [28,33,34] and in vitro [22,[35][36][37]. To date, there are few, inconsistent data on the antioxidant role of PRP on tenocytes and tendon healing [22,38,39] so far.…”
Section: Discussionmentioning
confidence: 99%